External validation of the 8th American Joint Committee on Cancer staging system for gall bladder carcinoma - Oweira, Hani; Mehrabi, Arianeb; Giryes, Anwar; Tekbas, Aysun; Abdel-Rahman, Omar (Journal of gastrointestinal oncology, 2018)
Background: To validate the changes within the American Joint Committee on Cancer (AJCC) 8 th staging system for gall bladder carcinoma compared to AJCC 7 th staging system. - Methods: Surveillance, Epidemiology and End Results (SEER) database [2004-2014] was queried. Kaplan-Meier survival analyses and Log-rank testing were assessed according to both AJCC 7 th and 8 th staging systems. Likewise, Cox cancer-specific hazard ratio was evaluated according to both staging systems. - Results: Overall survival was assessed according to the two staging systems; and P values for overall trend (log/rank test) were significant (P<0.001) for both scenarios. Cox regression cancer-specific hazard adjusted for age, gender, histology, gender and surgery was evaluated according to the two staging systems. According to AJCC 7 th staging system, the following pair wise hazard ratio comparisons were significant (II vs . IIIA; IIIB vs . IVA; IVA vs . IVB). According to AJCC 8 th staging system, the following pair wise hazard ratio comparisons were significant (II vs . IIIA; IVA vs . IVB). C-statistic was assessed using death from gall bladder carcinoma as the dependent variable; and the findings for the two staging systems were as follows: AJCC 7 th staging system: 0.684 (SE: 0.008; 95% CI: 0.667-0.701); AJCC 8 th staging system: 0.682 (SE: 0.009; 95% CI: 0.665-0.698). - Conclusions: There is a comparable discriminatory performance for AJCC 8 th staging system compared to AJCC 7 th staging system. Change form location-based to number-based N category assessment does not improve the overall prognostic performance of the staging system.
Gesehen am 11.03.2020